The mediating role of children's intergenerational support in association between grandparenting and cognitive function among middle-aged and older Chinese: findings from the CHARLS cohort study - Xuebei Hou; Yujun Luo; Fen Yang; Xinhong Zhu; Xiaolian Gao; Wenqiang Wang; Guiyuan Qiao; Jing Zhou (BMC, 2024)
Abstract Objectives With the world's population increasing in age, there has been a significant rise in the prevalence of cognitive impairment and dementia among individuals. This study aims to investigate the association between grandparenting and cognitive function among middle-aged and older Chinese using data from 2011 to 2018 China Health and Retirement Longitudinal Study (CHARLS). Additionally, the study seeks to explore the potential mediating effect of intergenerational support from children on this relationship, using data from the CHARLS 2011 database. Methods 5254 participants were recruited at the baseline survey in CHARLS 2011. Subsequently, a follow-up survey was conducted over 8 years, from CHARLS 2011 to 2018, with 1472 individuals completing the follow-up survey. The CHARLS included surveys on grandparenting and cognitive assessments. Grandparenting was categorized as yes and no. The assessment of cognitive function involved the evaluation of episodic memory and mental intactness. The present study used cross-sectional and longitudinal analyses to examine the relationship between grandparenting and cognitive function. The bootstrap method assessed the mediating effect of children's intergenerational support. Results The results of both cross-sectional and longitudinal studies indicated a positive association between grandparenting and cognitive function in middle-aged and older Chinese (B = 0.138, p < 0.05; B = 0.218, p < 0.05). Children's emotional and economic support played intermediary roles between grandparenting and cognitive function. Conclusion The results emphasized the significance of policymakers considering the consequences of intergenerational care and family support when formulating and executing social service policies targeted at the middle-aged and older population in China.